YTHDF1 phase separation triggers the fate transition of spermatogonial stem cells by activating the IκB-NF-κB-CCND1 axis - Qian Fang; Geng G. Tian; Qian Wang; Mengyao Liu; Lin He; Shengtian Li; Ji Wu (Cell Reports, 2023)
Summary: N6-methyladenosine (m6A) modification controls cell fate determination. Here, we show that liquid-liquid phase separation (LLPS) of YTH N6-methyladenosine RNA binding protein 1 (YTHDF1), a pivotal m6A “reader” protein, promotes the transdifferentiation of spermatogonial stem cells (SSCs) into neural stem cell-like cells by activating the IκB-nuclear factor κB (NF-κB)-CCND1 axis. The inhibition of IκBα/β mRNA translation mediated by YTHDF1 LLPS is the key to the activation of the IκB-NF-κB-CCND1 axis. Disrupting either YTHDF1 LLPS or NF-κB activation inhibits transdifferentiation efficiency. Moreover, overexpression of the YTH domain of YTHDF1 inhibits the activation of the IκB-NF-κB-CCND1 axis by promoting IκBα/β mRNA translation. Overexpression of the tau-YTH fusion protein reactivates IκB-NF-κB-CCND1 axis by inhibiting the translation of IκBα/β mRNAs, and tau LLPS is observed, which can restore transdifferentiation efficiency. Our findings demonstrate that the protein-RNA LLPS plays essential roles in cell fate transition and provide insights into translational medicine and the therapy of neurological diseases.